Factors Affecting Sexual History Taking in a Health Center Serving Homeless Persons. (July 2018) - Sowicz, Timothy Joseph; Bradway, Christine K.
Low rates of documentation of sexual histories have been reported and research on sexual history taking (SHT) has focused on the content of, barriers to collecting, and interventions to improve documentation of sexual histories. Absent from this literature is an understanding of the contextual factors affecting SHT. To address this gap, a focused ethnography of one health center was conducted. Data were collected through observations of health care encounters and interviews with health care providers (HCPs). No SHT was observed and this was likely influenced by patients' characteristics, communication between patients and HCPs, the prioritization of patients' basic needs, and time constraints imposed upon encounters. Given that the health center studied serves patients experiencing homelessness, behavioral health concerns, and opioid use disorder, findings illuminate areas for future inquiry into a patient population affected by social as well as physiologic determinants of health and potentially at high risk for adverse sexual health outcomes.